Cryotherapy versus CO2 laser in the treatment of plantar warts: a randomized controlled trial - Nahid Hemmatian Boroujeni (Mattioli1885, 2018)
Background: Warts are one of the most common infections in humans. Plantar warts are a subtype of non-genital warts, and several procedures and topical treatments have been used in its treatment. Cryotherapy is one of the most popular modalities, but it is time-consuming and remission rates vary in different studies. CO2 laser was the first laser used for treating warts. To date, no clinical trial has been done to compare CO2 laser with cryotherapy in the treatment of plantar warts.